Efeito dos colírios hialuronato de sódio (0,15%) e carboximetilcelulose sódica (0,5%) no tempo de ruptura do filme lacrimal de cães com ceratoconjuntivite seca e cães saudáveis e o efeito do colírio hialuronato de sódio (0,15%) em gatos saudáveis antes e após a anestesia geral - Madruga, Gabriela Morais (2017)
This study aimed to evaluate the effect of the 0.15% sodium hyaluronate (SH) and of 0.5% carboxymethylcellulose (CMC) on tear film breakup time (TFBUT) in 10 healthy dogs and in 32 eyes of dogs with keratoconjunctivis sicca (KCS). In addition, the goblet cell density (GCD) of this population was quantified. TFBUT was assessed at baseline and at different time points following the instillation of SH and CMC. KCS was graded as mild, moderate and severe. GCD were quantified from conjunctival biopsies. The number of GCD differed significantly between patients with mild and moderate KCS (P<0.01). TFBUT of healthy dogs increased only at 1 minute after treatment with SH (P<0.01). Regarding baseline and treatments, SH significantly increased TFBUT for up to 30 minutes on the ocular surface, in comparison to CMC, in all categories of KCS (P<0.01). TFBUT and GCD correlated positively when the healthy and diseased eyes were grouped (r=0.41, P=0.006). It can be concluded that in GCD the TFBUT showed that the tear film stability tends to reduce in a linear fashion from the mild to severe form of KCS. And in dogs with KCS, SH lasts longer periods on the ocular surface than CMC, but such agents does not increase TFBUT in healthy dogs.